PENDIDIKAN KESEHATAN TENTANNG BAHAYA MPASI DINI BAGI TUMBUH KEMBANG BAYI DI DESA PADELEGAN - Nur Karina; Yulia Paramita Rusady (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
Giving complementary foods (MPASI) before the age of 6 months still happens quite often and can cause various health problems, such as digestive issues, increased risk of infections, and less optimal infant development. Therefore, it is very important to provide education for parents. This community service activity aims to improve parents’ knowledge about the dangers of giving MPASI too early as well as the correct practices of MPASI based on health recommendations. The methods used include interactive counseling sessions, distribution of educational leaflets, demonstrations of appropriate MPASI textures according to age, and evaluations through pre-tests and post-tests. The results showed a significant increase in participants’ understanding of the risks of early MPASI, their ability to recognize danger signs, and their knowledge of proper MPASI principles in terms of texture, feeding frequency, and nutritional content. In conclusion, this educational program is effective in increasing parents’ knowledge and can help prevent early MPASI practices, thereby supporting optimal infant growth and development.ABSTRAKPemberian MPASI sebelum usia 6 bulan masih sering terjadi dan bisa menimbulkan berbagai masalah kesehatan, seperti gangguan pencernaan, lebih rentan terkena infeksi, dan perkembangan bayi yang tidak optimal. Karena itu, penting banget untuk memberikan edukasi kepada orang tua. Kegiatan pengabdian ini bertujuan untuk meningkatkan pengetahuan orang tua tentang bahaya pemberian MPASI terlalu dini serta cara pemberian MPASI yang benar sesuai dengan rekomendasi kesehatan. Metodenya meliputi penyuluhan interaktif, pembagian leaflet edukasi, demonstrasi tekstur MPASI sesuai usia, serta evaluasi lewat pre-test dan post-test. Hasilnya menunjukkan adanya peningkatan yang signifikan dalam pemahaman peserta tentang risiko MPASI dini, kemampuan mengenali tanda bahaya, dan pengetahuan tentang prinsip pemberian MPASI yang benar dari segi tekstur, frekuensi, dan kandungan gizinya. Jadi, bisa disimpulkan bahwa edukasi ini efektif meningkatkan pengetahuan orang tua dan bisa mencegah pemberian MPASI dini, yang tentunya mendukung tumbuh kembang bayi secara optimal.